2011
DOI: 10.4137/cmo.s4907
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin: Safety and Efficacy in the Treatment of Advanced Sarcoma

Abstract: Soft tissue sarcomas (STS) are a rare group of malignancies with multiple different subtypes. Close to half of intermediate or high grade STS develop metastatic disease. Treatment of recurrent/metastatic sarcomas is quite challenging with only a few drugs showing measurable benefits. Trabectedin (ecteinascidin 743, ET-743, Yondelis) is a newly developed alkylating agent that has shown significant broad spectrum potential as a single agent second line drug alone or in combination particularly in the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The results were comparable to previous reports (13,14,16,19,20). Notably, although patients with L-sarcoma tended to have better PFS than non-L-sarcoma patients, neither L-sarcoma nor TRS significantly affected the efficacy of trabectedin in terms of prognosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results were comparable to previous reports (13,14,16,19,20). Notably, although patients with L-sarcoma tended to have better PFS than non-L-sarcoma patients, neither L-sarcoma nor TRS significantly affected the efficacy of trabectedin in terms of prognosis.…”
Section: Discussionsupporting
confidence: 87%
“…Trabectedin is a marine-derived, semisynthetic DNAbinding protein that exerts an antineoplastic effect by binding to the minor groove of DNA and bending the DNA towards the main groove (12). This agent has been approved for clinical use in Europe since 2007 and has been used to treat patients with unresectable advanced or recurrent STS (13,14). Following a clinical trial targeting translocation-related sarcoma (TRS), trabectedin was finally approved in Japan in 2015.…”
mentioning
confidence: 99%
“… 99 , 100 Adverse effects of trabectedin include neutropenia, transaminase elevation, fatigue and emesis. 101 The success of trabectedin in early clinical trials led to its approval by the European Union for advanced soft tissue sarcoma in 2007 and subsequently the drug has been approved in over 70 countries, especially for patients who have failed to respond to standard therapies. 102 – 104 A recent phase III clinical trial confirmed that advanced liposarcoma and leiomyosarcoma refractory to doxorubicin and ifosfamide showed a 45% reduction in the risk of disease progression or death when treated with trabectedin in comparison with darcarbazine, which prompted the approval of trabectedin by the US Food and Drug Administration (FDA).…”
Section: Systemic Control In Sarcomamentioning
confidence: 99%
“…Trabectedin binds to the minor groove of DNA with preference for GC-rich triplets and subsequently forms covalent adducts with the N2-position through its carbinolamine moiety [ 158 , 159 , 160 ]. ET-743, under the trade name Yondelis, was approved for the treatment of refractory soft-tissue sarcomas by the European Commission in July 2007; the currently ongoing Phase III trials along with the already existing clinical evidence may provide enough data for the Food and Drug Administration for an approval in the US [ 161 ]. Based on the preclinical results, trabectedin is also being developed for ovarian, prostate, lung, breast and pediatric cancers [ 149 , 162 , 163 ].…”
Section: Tyrosine- and Phenylalanine-derived Alkaloidsmentioning
confidence: 99%